2012
DOI: 10.1103/physrevb.85.205135
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy plasmonic structure in CaC6

Abstract: The low-energy dielectric properties of CaC 6 -a representative graphite intercalated compound (GIC)-were investigated by ab initio time-dependent density functional theory calculations with full inclusion of local field effects. The calculations predict the existence of several kinds of plasmons in CaC 6 with energy below 10 eV. The mode with the largest energy is a conventional "πp" mode strongly dispersing in the hexagonal basal plane and almost nondispersing in the perpendicular direction. In the 2.3-3 eV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 73 publications
6
38
0
Order By: Relevance
“…The latter can act to screen the repulsion between the former, resulting in the appearance of a plasma mode with a soundlike dispersion. This is, for instance, what has been proved in MgB 2 [33], which has two bands with π (fast carriers) and σ (slow carriers) character that are metallic (i.e., cross the Fermi energy) or in other materials such as CaC 6 [34], Pb [35], and Pd [36]. With respect to this, 2H-TMD are similar to MgB 2 since the d z 2 and p z bands can play the same role of the σ and π bands, respectively.…”
Section: Out-of-plane Loss Functionmentioning
confidence: 98%
“…The latter can act to screen the repulsion between the former, resulting in the appearance of a plasma mode with a soundlike dispersion. This is, for instance, what has been proved in MgB 2 [33], which has two bands with π (fast carriers) and σ (slow carriers) character that are metallic (i.e., cross the Fermi energy) or in other materials such as CaC 6 [34], Pb [35], and Pd [36]. With respect to this, 2H-TMD are similar to MgB 2 since the d z 2 and p z bands can play the same role of the σ and π bands, respectively.…”
Section: Out-of-plane Loss Functionmentioning
confidence: 98%
“…57 We relay the appearance of this peak to the existence of a low-energy acoustic plasmon, also predicted to exist on base of the first-principles calculations in other systems such as MgB 2 and Pd. 31,58 Previously such kind of plasmon was intensively investigated in various layered systems [23][24][25][26][27][28][29][30][31][32][33][34] and other materials with two kinds of carriers at the Fermi level. [59][60][61][62][63][64] The appearance of this plasmon is related to the presence of two kinds of charge carriers characterized by different maximal Fermi velocity components in a given direction in the energy bands crossing the Fermi surface.…”
Section: E Role Of Lf Effectsmentioning
confidence: 99%
“…22 At the same time, there is a rich literature on plasmons in other layered systems like semiconductor superlattice structures, [23][24][25][26][27][28] high-T c oxides, 29,30 MgB 2 , 31 other layered superconductors, 32,33 and intercalated graphite. 34 In these studies it was demonstrated that the presence of the layered structure leads to strong modifications in the plasmon spectrum in comparison with that of a homogeneous three-dimensional electron gas. Thus in addition to the conventional bulk plasmon the existence in such systems of an additional mode with characteristic soundlike dispersion was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Very often, these transitions play an important role in the formation of excitation spectrum; in particular, of plasmon properties. For instance, the intraband transitions within several partly occupied energy bands induce low-energy plasmons with characteristic sound-like dispersion in some materials [20,21,[33][34][35]. The interband transitions give rise to a strong redshift of the Ag plasmon frequency [36,37] or to a negative momentum dispersion [38,39] of the plasmon in heavy alkali metals [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The interband transitions give rise to a strong redshift of the Ag plasmon frequency [36,37] or to a negative momentum dispersion [38,39] of the plasmon in heavy alkali metals [40,41]. Moreover, these transitions dominate the energy-loss landscape in the low-energy-transfer domain in many materials like MgB 2 [15,16], intercalated graphite [35,42], transition-metal dichalcogenides [20,21,[43][44][45], lead [31], and Heusler compounds [46].…”
Section: Introductionmentioning
confidence: 99%